Risk factors in caprine lentivirus transmission through semen - Andrioli, Alice; Gouveia, Aurora Maria Guimarães; Martins, Almir de Sousa; Pinheiro, Raymundo Rizaldo; Santos, Diones Oliveira (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the presence of the DNA provirus of the caprine lentivirus (LVC) in ejaculates of naturally infected males, and to verify the influence of the wash of the semen as well as the presence of testicle inflammation on the viral load. Eight semen collections of seven soropositive reproducers were accomplished, four before testicle injury and four after injury. Amongst the collections carried out at the same week, in one the ejaculate was washed, to withdraw the plasma seminal, and in the other it was not. The provirus DNA was identified both by Nested polymerase chain reaction technique (Nested PCR) and by the viral isolation. The virus was isolated in 7.1% of the samples. The PCR identified the provirus DNA in 35.7% of all samples, 17.9% in the washed samples and 53.6% of the integral semen samples. The injury of the testicle tends to greater flow of virus for the semen, therefore, before injury, 21.4% of the samples were positive and after-injury, 50%. Risk of transmission of the LVC by semen of goat reproducers is strengthened by the presence of testicle inflammations and the fact that the criopreserved semen contains the LVC in infecting form.